Improvement and determination of the influencing factors of coiled tubing fatigue life prediction. (September 2019) - Zhou, Zhao-ming; Tan, Jin-song; Wan, Fu; Peng, Bo
The fatigue life prediction model cannot accurately predict the service life of coiled tubing operations, resulting in waste and accidental fracture of coiled tubing. This article introduces the fatigue life prediction model of coiled tubing and a detection system developed using weak magnetic detection method and eddy current detection method. The detection device is used to detect accurate defect dimension, wall thickness reduction, and diameter deformation to improve the accuracy of fatigue life prediction. Furthermore, the actual defect dimension is included in the fatigue life assessment calculation to eliminate the influence of the existing model on the immobilization of defects and corrosion influence factors. By analyzing field operation cases and measured values, the effects of defects, wall thickness reduction, and diameter growth on fatigue life are studied to improve the accuracy of parameters and the integrity of basic data in the calculation process. The influence of reverse bending and weld on fatigue life is discussed. The residual life can be predicted more accurately by combining field testing technology and fatigue life evaluation method. Field measurement input of fatigue life prediction model is the main means to improve its accuracy and practicability.